Three‐Dimensional (3‐D) Printing: A Cost‐Effective Solution for Improving Global Accessibility to Prostheses. Issue 12 (18th December 2015) - Silva, Kyle; Rand, Stephanie; Cancel, David; Chen, Yuxi; Kathirithamby, Rani; Stern, Michelle
Abstract: The lack of access to prostheses is a global problem, partially caused by the high cost associated with the current manufacturing process. Three‐dimensional printing is gaining use in the medical field, and one such area is prosthetics. In addition to using cost‐effective materials, this technology allows for rapid prototyping, making it an efficient solution for the development of affordable prostheses. If the rehabilitation medicine community embraces this novel technology, we can help alleviate the global disparity of access to prostheses.